IDENTIFIKASI GEOMETRI BIDANG PADA POLA MOTIF KAIN TENUN SOLOK BANYUWANGI - Seli Wahyutini Khoiriyah; Sunardi Sunardi; Erfan Yudianto (saintifika, 2020)
A culture is born from the local community so as to produce works that become the characteristic of the culture. This culture is rooted and develops over time. One result of cultural work is Banyuwangi solok weaving. Education appreciates local culture in order to participate in preserving through the teaching and learning process. Weaving Solok Banyuwangi can be included as a medium for student learning in schools. Mathematics is one branch of science that studies symbols with logical reasoning. So there are estimates of the mathematical elements found in the Banyuwangi solok weaving motif. Mathematical elements found in Banyuwangi solok weaving include points, lines, triangles, quadrilaterals, hexagon, folding symmetry, rotary symmetry, congruence and similarity.